Efficacy of breast Lump Examination Orientation Module (BLOM) To Aware Women in the WardhaDistrict: Life Sciences-Ayurveda - Sanjay Ingole, Shivani; Pradnya Dandekar, Dr. (International Journal of Life Science and Pharma Research, 2023)
Day by day the prevalence of Breast Cancer is increasing. Early diagnosis and intervention is best solution for this. Due to unaware about the knowledge for early diagnosis techniques like breast self-examination (BSE) many women miss out on early detection and treatment opportunities. So to orient them about the process of examination the module is prepared. –To evaluate the efficacy of Breast Lump Examination Orientation Module (BLOM) to aware women in Wardha district this study was undertaken. Randomly the females in between age group 15 to 50 years were selected for the study. After taking their informed consent they were oriented regarding the technique of self-breast examination through the BLOM module.–A structured and validated questionnaire was prepared for Pre & post test. The data was analyzed on the basis of learning gain. The feedback on five point liker scale was also analysed. The absolute learning gain was found to be 65.29.:It was concluded that the module is significantly efficient to orient women regarding breast lump examination techniques.